Cerebellum and cognition: Evidence for the encoding of higher order rules - BALSTERS, JOSHUA; ROBERTSON, IAN (My University, 2013)
Converging anatomical and functional evidence suggests that the cerebellum processes both motor and nonmotor information originating from the primary motor cortex and prefrontal cortex, respectively. However, it has not been established whether the cerebellum only processes prefrontal information where rules specify actions or whether the cerebellum processes any form of prefrontal information no matter how abstract. Using functional magnetic resonance imaging, we distinguish between two competing hypotheses: (1) activity within prefrontal-projecting cerebellar lobules (Crus I and II) will only be evoked by rules that specify action (i.e. first-order rules; arbitrary S–R mappings) and (2) activity will be evoked in these lobules by both first-order rules and second-order rules that govern the application of lower order rules. The results showed that prefrontal-projecting cerebellar lobules Crus I and II were commonly activated by processing both first- and second-order rules. We demonstrate for the first time that cerebellar circuits engage both first- and second-order rules and in doing so show that the cerebellum can contribute to cognitive control independent of motor control.
PUBLISHED
Keywords: cerebellum; cognition; fMRI; prefrontal cortex; rule retrieval